Evaluation of vegetable protein in canine diets: assessment of performance and apparent ileal amino acid digestibility using a broiler model - Fiacco, D.C.; Lowe, J.A.; Wiseman, J.; White, G.A. (Wiley, 2017)
Recent technological advances in the human food industry with respect to meat processing have decreased the availability of animal proteins to the pet food industry which typically formulates diets with an excess of animal protein. In the long term, this is not sustainable; thus, alternative protein sources need to be investigated. This study examined three canine diets, comparing a typical animal protein-based diet (control) with two experimental diets where the animal protein was substituted in part with vegetable protein (formulated based either on total protein or amino acid content) using a broiler model. Each diet was fed to six cages each containing two birds from day 15, 18 cages in total (36 birds). Excreta were collected from days 19 to 21. On day 23, birds were euthanized and weighed, and their ileal digesta were collected and pooled for each cage. In addition, one leg per cage was collected for evaluation of muscle mass. Results showed no significant difference in animal performance (feed intake or live weight gain) or muscle to leg proportion across the diets. Birds fed the control diet and the diet balanced for amino acid content exhibited the greatest coefficients of apparent metabolizability for nitrogen (p < .001). Birds fed the diets that contained partial replacement of animal with vegetable protein generally had greater ileal digestibility of amino acids compared to birds fed the control (animal protein) diet. Analysis of excreta showed no dietary difference in terms of dry matter content; however, birds fed the diet balanced for total protein and the diet balanced for amino acid content had significantly greater excreta nitrogen than the control (p = .038). Overall, the study suggests vegetable proteins when formulated based on amino acid content are a viable alternative to animal proteins in canine diets.